Perceptions of Select Filipino Teachers on the Most Essential Learning Competencies (MELCs) of the K to 12 Curriculum - Montebon, Darryl Roy (Community and Social Development Journal, 2024)
The effects of Covid-19 on schools have been substantial and widespread. The impact of these changes has been far-reaching, affecting students and teachers alike. Strategically, the Department of Education in the Philippines released a concise version of the K to 12 curriculum to include only the Most Essential Learning Competencies or the MELCs. In effect, the researcher determined the perception of the teachers on the MELCs. Through a survey of 173 teachers across the Country, the findings revealed that teachers moderately agreed on statements related to impression (M=2.71, SD=0.44), morale (M=2.60, SD=0.36), stress, and workload (M=2.63, SD=0.35). Lastly, there was no significant difference in the perception of teachers as to gender, gender, years of teaching experience, type of school, and academic backgrounds.